3D bioprinted scaffolds of polysaccharide hydrogels in osteochondral and cartilage tissue engineering - Jianghong Huang; Zhiwang Huang; Jianyi Xiong; Jiang Xia; Youquan Wang; Lei Yang; Yujie Liang (Designed Monomers and Polymers, 2023)
The construction of bioactive scaffolds with a suitable microenvironment for tissue regeneration provides a great promise for improving clinical treatment of osteochondral and full-thickness articular cartilage defects. Hydrogels of polysaccharides, such as alginate, agarose, chitosan, cellulose, hyaluronic acid, and dextran, biomimic the structure of the extracellular matrix (ECM), are exceptionally biocompatible scaffold material for tissue regeneration. The application of polysaccharide hydrogels combined with 3-dimensional (3D) printing technology can precisely distribute cell-loaded biomaterials, construct complex 3D living tissues with optimal structure and mechanical properties for osteochondral and cartilage repair. This review highlights recent advances in the development of polysaccharide-based hydrogel materials for promoting bone and cartilage tissue repair. We also highlight recent advances in 3D bioprinting polysaccharide-based hydrogel materials in cartilage regeneration. The cell type and the development of 3D bioprinting technology were described. In addition, the formation of polysaccharide – protein-based is also discussed. We outline the future trends of 3D printing including machine learning, near-infrared photopolymerization, 4D printing, and a combination of self-assembly and live-cell 3D printing-based methods.